1963
DOI: 10.1152/ajplegacy.1963.205.4.693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbonic anhydrase inhibition on proximal tubular bicarbonate reabsorption

Abstract: Samples of fluid from the proximal tubule were collected for the measurement of pH and bicarbonate concentration before and after the administration of acetazolamide (Diamox). Samples collected before acetazolamide were consistently more acid than plasma with the most acid samples coming from the more distal portion of the proximal tubule. After the intravenous administration of acetazolamide, the pH and bicarbonate concentration were consistently higher than in plasma. Bicarbonate concentrations as high as 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

1964
1964
1976
1976

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…The proximal tubule, therefore, unlike the distal tubule, does not demonstrate a reciprocal relationship between hydrogen and potassium ion secretion. These results confirm similar observations made in rodents (2,16).…”
Section: Discussionsupporting
confidence: 93%
“…The proximal tubule, therefore, unlike the distal tubule, does not demonstrate a reciprocal relationship between hydrogen and potassium ion secretion. These results confirm similar observations made in rodents (2,16).…”
Section: Discussionsupporting
confidence: 93%
“…Strong support for this assumption was given by Pitts and Lotspeich11 and Rector et al 16 However, Clapp et al12 opposed these opinions, who found the Diamox-inhibition in the whole nephron, especially, in the proximal tubules. This was reconfirmed by Rector et al17 In brief, the findings in this study favor the opinion of Clapp et al 12 Principal point of my results is that the CAH activity is most concentrated in the proximal tubules, while the distal tubules show a moderate, but far less concentrated amount of CAH. The specificity of the histochemical technique used here may be supported by the completely negative reaction in the sections treated with the substrate medium containing a small amount of Diamox.…”
Section: Discussionsupporting
confidence: 90%
“…This postulation is supported by the data of Agus and co-workers (6,7) in micropuncture experiments that both PTH and its cellular messenger, cyclic AMP, inhibit proximal tubular reabsorption of phosphate, sodium, and water. Inhibition of carbonic anhydrase by pharmacological agents, such as acetazolamide, also inhibits proximal tubular reabsorption of phosphate, sodium, and water (8)(9)(10)(11) as well as bicarbonate (12)(13)(14)(15)(16)(17). The qualitative similarity between the inhibition of proximal tubular reabsorption of those ions after the PTH administration and that after the inhibition of carbonic anhydrase by acetazolamide suggests that at least a part of renal effect of PTH is mediated through the inhibition of carbonic anhydrase in proximal tubules.…”
Section: Introductionmentioning
confidence: 99%